Combined induction by Cu(II) and veratrole enhances the degradation of high molecular weight polyaromatic hydrocarbons by Fusarium dlaminii ZH-H2 - Jiayuan Gao; Mingyue Qi; Xiaomin Wang; Xuan Feng; Jiahui Li; Guangwei Zhang; Shengdong Feng; Zhixin Yang; Guohui Ning (Ecotoxicology and Environmental Safety)
The effect of combined induction by Cu(II) and veratrole on the degradation of high molecular weight polyaromatic hydrocarbons (HMW-PAHs) by Fusarium sp. ZH-H2 was investigated. This strain was characterized as F. dlaminii. The combination treatment of Cu(II) with veratrole (CL) improved the degradation efficiency of a mixture of 10 HMW-PAHs by 16 % compared to the control without inducer (CK), by 5 % compared to single Cu(II) induction (C), and by 12 % compared to single veratrole induction (L). In particular, degradation of benzo(g,hi)perylene (BghiP) was improved by 36 % compared to CK and by 52 % compared to L. The CL combination treatment increased lignin peroxidase (LiP) activity by 162 % at day 5 of incubation compared to the control and by 277 % compared to C. Transcriptome analysis revealed that the expression of 910 Fusarium genes had changed as a result of the combination treatment, with 510 up-regulated genes and 443 down-regulated genes. The combined CL treatment not only significantly stimulated Lip activity, but also induced the expression of genes coding for non-ligninolytic enzymes, which contributed to the degradation of PAHs. These included cytochrome P450 monooxygenase (EC:1.–.-.-) and downstream PAH converting enzymes such as aldehyde dehydrogenase (EC:1.2.1.3), NADP-dependent ethanol dehydrogenase (EC:1.1.1.2), ethanol dehydrogenase (EC:1.1.1.156], tryptophan 2,3 dioxygenase (EC:1.13.11.52), gentisate 1,2-dioxygenase (EC:1.13.11.5), salicylate hydroxylase (EC:.14.13.1) β-hexokinase (EC:3.2.1.52), and glutathione transferase (EC: 2.5.1.18). Their increased expression enhanced the HMWPAHs degradation under induction of Cu(II) plus veratrole synergistically. These findings provide new insights in the combined use of these inducers for enhanced microbial remediation of HMW-PAHs in the environment.